UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATERI LISTRIK DINAMIS DI SMAN 13 BUNGO - Adha, Al Fajri; Syefrinando, Boby; Sulman, Fauzan (Physics and Science Education Journal (PSEJ), 2025)
This research aims to describe efforts to improve student learning outcomes by using the Project Based Learning (PjBL) learning model for class XII MIPA students on Dynamic Electricity material at SMAN 13 Bungo. This research is classroom action research carried out in two cycles, where each cycle is carried out in two meetings and consists of four stages, namely action planning, action implementation, observation and evaluation, and ending with reflection. The subjects of this research were 33 students of class XII MIPA SMAN 13 Bungo, consisting of 19 students and 14 female students. The data analysis techniques used are qualitative and quantitative. The research results show that the project based learning (PjBL) learning model is effective in improving student learning outcomes in dynamic electricity subjects. Efforts to improve student learning outcomes by using observation data and end-of-cycle assessments in the form of essay questions, in cycle I obtained an average student score of 69.2 with 10 students succeeding with a student success percentage of 30.3%. In cycle II students obtained an average score of 82.2 with the number of successful students being 29 people with a student success percentage of 87.9%. Student activity and teacher activity during the learning process also increased. Based on the results of research that has been conducted, it can be concluded that the project-based learning model has proven capable and successful in improving student learning outcomes.